2012
DOI: 10.1002/adfm.201102907
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Gelatin Microgels by a “Cast” Strategy for Controlled Drug Release

Abstract: In this paper, we propose a “casting” strategy to prepare intrinsically fluorescent, uniform and porous gelatin microgels with multi‐responsiveness. Gelatin microgels with tunable size were obtained by copying the structure of a porous CaCO3 template. The diameter of the gelatin microgels was sensitive to salt concentration and pH. Doxorubicin and Rhodamine B as model drugs were loaded into the microgels via electrostatic interaction and release of the payload was triggered by changing the salt concentration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 48 publications
0
46
0
Order By: Relevance
“…However, due to the consumption of primary amines during crosslinking and the addition of negatively charged genipin [20], both gel types in the current experiment have been altered to possess a negative net charge for attracting cationic growth factors. Other studies have reported similar zeta potentials of gelatin carriers ranging from −9 mV [16] to −13 mV [46] at physiological pH.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…However, due to the consumption of primary amines during crosslinking and the addition of negatively charged genipin [20], both gel types in the current experiment have been altered to possess a negative net charge for attracting cationic growth factors. Other studies have reported similar zeta potentials of gelatin carriers ranging from −9 mV [16] to −13 mV [46] at physiological pH.…”
Section: Resultsmentioning
confidence: 74%
“…After the initial burst-release of unbound growth factor, spontaneous release due to gradual diffusion, in the absence of degradation, was also found to be minimal with both GelA and GelB carriers. Other factors such as temperature [8], and solution ion concentration [8,46], pH [46], and may affect the conformation of the gelatin carrier or electrochemical affinity with loaded proteins. Microspheres were loaded overnight at 37 °C to maximize molecular mobility, optimizing swelling and growth factor uptake [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microgels are microscopic hydrogel particles with tunable biological, chemical and mechanical properties [1, 2]. Natural structural biomaterials such as bone, horn, nail, skin, feather and hair are structures of self-assembled protein molecules [3].…”
Section: Introductionmentioning
confidence: 99%
“…Genipin and transglutaminase (Tgase) were used to increase the crosslink density. Genipin is a crosslinker that has been used previously in combination with, for example, chitosan [26] [184] and the proteins gelatin; [26] [174] bovine serum albumin; [26] β-lactoglobulin; [121] and casein. [136] Crosslinking of proteins by genipin follows a two-step reaction with the primary amino groups of the proteins, resulting in a blue colour.…”
Section: 1mentioning
confidence: 99%